Modulating Activity of Vancomycin and Daptomycin on the Expression of Autolysis Cell-Wall Turnover and Membrane Charge Genes in hVISA and VISA Strains - Cafiso, Viviana; Bertuccio, Taschia; Spina, Daniela; Purrello, Simona; Campanile, Floriana; Di Pietro, Cinzia; Purrello, Michele; Stefani, Stefania (PLOS ONE, 2012)
Glycopeptides are still the gold standard to treat MRSA (Methicillin Resistant Staphylococcus aureus) infections, but their widespread use has led to vancomycin-reduced susceptibility [heterogeneous Vancomycin-Intermediate-Staphylococcus aureus (hVISA) and Vancomycin-Intermediate-Staphylococcus aureus (VISA)], in which different genetic loci (regulatory, autolytic, cell-wall turnover and cell-envelope positive charge genes) are involved. In addition, reduced susceptibility to vancomycin can influence the development of resistance to daptomycin. Although the phenotypic and molecular changes of hVISA/VISA have been the focus of different papers, the molecular mechanisms responsible for these different phenotypes and for the vancomycin and daptomycin cross-resistance are not clearly understood. The aim of our study was to investigate, by real time RT-PCR, the relative quantitative expression of genes involved in autolysis (atl-lytM), cell-wall turnover (sceD), membrane charges (mprF-dltA) and regulatory mechanisms (agr-locus-graRS-walKR), in hVISA and VISA cultured with or without vancomycin and daptomycin, in order to better understand the molecular basis of vancomycin-reduced susceptibility and the modulating activity of vancomycin and daptomycin on the expression of genes implicated in their reduced susceptibility mechanisms. Our results show that hVISA and VISA present common features that distinguish them from Vancomycin-Susceptible Staphylococcus aureus (VSSA), responsible for the intermediate glycopeptide resistance i.e. an increased cell-wall turnover, an increased positive cell-wall charge responsible for a repulsion mechanism towards vancomycin and daptomycin, and reduced agr-functionality. Indeed, VISA emerges from hVISA when VISA acquires a reduced autolysis caused by a down-regulation of autolysin genes, atl/lytM, and a reduction of the net negative cell-envelope charge via dltA over-expression. Vancomycin and daptomycin, acting in a similar manner in hVISA and VISA, can influence their cross-resistance mechanisms promoting VISA behavior in hVISA and enhancing the cell-wall pathways responsible for the intermediate vancomycin resistance in VISA. Daptomycin can also induce a charge repulsion mechanism both in hVISA and VISA increasing the activity of the mprF.